2002
DOI: 10.1094/pdis.2002.86.3.330c
|View full text |Cite
|
Sign up to set email alerts
|

First Report of an Aster Yellows Subgroup 16SrI-B Phytoplasma Infecting Chayote in Costa Rica

Abstract: An outbreak of a witches' broom disease affected approximately 20% of plants in several chayote (Sechium edule (Jacq.) Schwartz) fields in the commercial production area of the Ujarrás Valley, Cartago Province, Costa Rica during 2000 and 2001. Affected chayote plants exhibited symptoms, including basal proliferation with severe foliage reduction, aborted flowers, and deformed fruits, suggestive of phytoplasmal infection. Two other symptomatic cucurbit species growing near the chayote fields were also identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
9
0
3
Order By: Relevance
“…This finding contributes knowledge about the diversity of phytoplasma diseases in Costa Rica and Central America, where the phytoplasmas detected are mainly related to groups 16SrI (Aster yellows group) (Lee et al, 2000;Villalobos et al, 2002;Saborío-R. et al 2007;Moreira et al 2010), 16SrIV (Coconut lethal yellows group) (Harrison et al, 2002;Roca et al, 2006) and 16SrIX (Pigeon pea witches'-broom group) (Kenyon et al, 1998(Kenyon et al, , 1999. New diseases related to other phytoplasma groups have been also reported in the last years, such as 16SrIII in El Salvador (Parada et al, 2006) and 16SrXXXI in Costa Rica (Villalobos et al, 2009;Lee et al, 2011).…”
supporting
confidence: 57%
See 2 more Smart Citations
“…This finding contributes knowledge about the diversity of phytoplasma diseases in Costa Rica and Central America, where the phytoplasmas detected are mainly related to groups 16SrI (Aster yellows group) (Lee et al, 2000;Villalobos et al, 2002;Saborío-R. et al 2007;Moreira et al 2010), 16SrIV (Coconut lethal yellows group) (Harrison et al, 2002;Roca et al, 2006) and 16SrIX (Pigeon pea witches'-broom group) (Kenyon et al, 1998(Kenyon et al, , 1999. New diseases related to other phytoplasma groups have been also reported in the last years, such as 16SrIII in El Salvador (Parada et al, 2006) and 16SrXXXI in Costa Rica (Villalobos et al, 2009;Lee et al, 2011).…”
supporting
confidence: 57%
“…The actual RFLP analysis with the endonucleases AluI, HaeIII, HpaII, Tru1I, TaqI (Figure 2-A), HinfI and Tsp509I (data not shown) of R16F2n/R16R2 PCR products generated patterns identical among the phytoplasmas under study but different from the RFLP pattern of phytoplasma infecting Sechium edule (subgroup 16SrI-B, Villalobos et al, 2002). The RFLP results indicated that the phytoplasma associated with GWB belonged to hibiscus witches' broom group (16SrXV), represented by 'Candidatus Phytoplasma (Ca.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…recientemente, los esfuerzos en la investigación fueron enfocados a la caracterización molecular del germoplasma, la identificación de nuevas razas de fitoplasmas y al establecimiento de las relaciones genéticas entre colectas con el fin de hacer un uso y conservación mas adecuado e identificar marcadores moleculares asociados con la respuesta al daño causado por estos patógenos (Villalobos et al 2002, Borth et al 2002, Lee et al 1998, Laviña y Battle 2002. a pesar del desarrollo de tecnologías basadas en el DNA, que permitieron contar con un mayor número de marcadores como los rFLPs y los basados en Pcr como son RAPD, SSR, AFLP (Milbourne et al 1997) en méxico no se han realizado estudios utilizando estas técnicas, pero se debe de considerar que los marcadores RAPDs tienen como desventaja no ser reproducibles entre laboratorios (Demeke et al 1993), aunque Pecina et al (2001) demostraron la factibilidad de su reprodubilidad.…”
Section: Introductionunclassified
“…afetadas pelo superbrotamento, em Taiwan (Lee et al, 1993). Na Costa Rica, um fitoplasma do grupo 16SrI foi identificado em campos comercias de chuchu e de Sechium tacaco, bem como na planta daninha Rytidostylis carthaginensis (Villalobos et al, 2002). Foi relatada ainda a ocorrência de um fitoplasma do grupo 16SrXII em plantas infectadas de Cucumis myriocarpus Naud., na Austrália (Saqib et al, 2006).…”
unclassified